Predictors of Outcome in Hospitalized Adult COVID-19 Patients Admitted to a Tertiary Hospital in Chattogram (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: The COVID-19 pandemic emerged as a major public health emergency affecting the healthcare services all over the world. It is essential to analyze the epidemiological and clinical characteristics of patients with COVID-19 in different parts of our country. This study highlights clinical experience in managing patients with COVID-19 at a tertiary care centre in southeastern Bangladesh.Materials and methods: Clinical characteristics and outcomes of consecutive 199 adult patients admitted to Chittagong Medical College Hospital, Chattogram, Bangladesh, from February 1 to March 31, 2021 were studied in this prospective observational study. The diagnosis of SARS-CoV-2 infection was confirmed by real-time reverse transcriptase polymerase chain reaction (RT-PCR) on throat and/or nasopharyngeal swabs. All patients were managed according to the hospital’s consensus protocol and in accordance with National Guidelines on clinical management of COVID-19.Results: The median age of the patients was 57 years (Range: 20-102 years) and 118 (59.3%) were male. One hundred and thirty two (67.3%) patients had associated comorbid condition and diabetes (44.7%) and hypertension (33.3%) were the most common. Majority (57.3%) was classified as having moderate severity and mortality of 10.1% (20 patients) was observed. Elderly age (>60 years), diabetes mellitus, elevated levels of D-dimer and neutrophillymphocyte ratio were the predictors of mortality.Conclusions: These findings suggest that the mortality rate in elderly COVID-19 patients with comorbidity is high and neutrophil-lymphocyte ratio could be a cost effective predictor of mortality in our context.JCMCTA 2022 ; 33 (1) : 138-143